MORPHOLOGICAL AND STRUCTURAL STUDY OF NANOPARTICLES OF CuO USING TECHNIQUES OF DISPERSION OF LIGHT AND X-RAY - Ríos, G. (2015)
Spherical cooper oxide (CuO) nanoparticles were synthetized by wet route using cooperacetate and sodium hydroxide. The CuO nanoparticles were characterized by dynamiclight scattering (DLS) and small angle X-ray scattering (SAXS). Furthermore to completestructural and morphological studies of the nanoparticles were performed X-ray diffractionand electron microscopy analysis. The results displayed that the CuO nanoparticles showedhigh dispersion; however, has a narrow size distribution for particles with size less than100 nm. Besides, the correlation between dispersion analysis, light and X-ray, and X-raydiffraction and electron microscopy was very good.